A Novel Dopant‐Free Triphenylamine Based Molecular "Butterfly" Hole‐Transport Material for Highly Efficient and Stable Perovskite Solar Cells. Issue 14 (17th May 2016) - Zhang, Fei; Yi, Chenyi; Wei, Peng; Bi, Xiangdong; Luo, Jingshan; Jacopin, Gwénolé; Wang, Shirong; Li, Xianggao; Xiao, Yin; Zakeeruddin, Shaik Mohammed; Grätzel, Michael
Abstract : A triphenylamine based molecular "butterfly" is developed as dopant‐free hole‐transport material for perovskite solar cells exhibiting excellent power conversion efficiency of 16.3% which is comparable to the state‐of‐the‐art doped 2, 2′, 7, 7′‐tetrakis( N, N ′‐di‐p‐methoxy‐phenylamine)‐9, 9′‐spirobifluorene ( spiro ‐OMeTAD). Moreover, the device is much more stable than that of spiro ‐OMeTAD based device under light irradiation.